2011
DOI: 10.1590/s0101-31222011000400014
|View full text |Cite
|
Sign up to set email alerts
|

Diferentes tipos de secagem: efeitos na qualidade fisiológica de sementes de pinhão manso

Abstract: LuiZ antônio dos santos dias 3 RESUMO -Objetivou-se no presente trabalho avaliar diferentes tipos de secagem e seus efeitos na qualidade fisiológica de sementes de pinhão manso (Jatropha curcas L.). As sementes, com teor de água de 32%, foram secas à sombra até 9,9%, ao sol até 8,8% e em estufa de circulação forçada às temperaturas de 33 °C até 8,5% e 43 °C até 8,3% A qualidade fisiológica das sementes foi avaliada pelos testes de germinação, primeira contagem de germinação, condutividade elétrica, envelhecime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
6
0
6
Order By: Relevance
“…Drying air temperature was approximately 55 °C and it did not immediately affect seed quality, agreeing with Costa et al (2012a) but contradicting results found by Costa et al (2012b), who reported that temperatures close to 60 °C is detrimental to the germination of crambe seeds. Zonta et al (2011) and Ullmann et al (2010) found no effect of drying temperatures respectively of 43 °C and 60 °C on the germination of Jatropha seeds.…”
Section: Resultsmentioning
confidence: 96%
“…Drying air temperature was approximately 55 °C and it did not immediately affect seed quality, agreeing with Costa et al (2012a) but contradicting results found by Costa et al (2012b), who reported that temperatures close to 60 °C is detrimental to the germination of crambe seeds. Zonta et al (2011) and Ullmann et al (2010) found no effect of drying temperatures respectively of 43 °C and 60 °C on the germination of Jatropha seeds.…”
Section: Resultsmentioning
confidence: 96%
“…This could lead to less harmful alteration to the seeds of fruits of the yellow and brownish-yellow stages and could consequently lower EC values. It was previously reported that rapid drying is better for J. curcas seed quality (Zonta, Araújo, Araújo, & Dias, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…The collected fruits had predominantly brown epicarps (Dranski et al 2010). The J. curcas fruits were dried in the shade for 45 days, with no control over temperature and humidity (Zonta et al 2011) to facilitate manual seed extraction from fruits.…”
Section: Methodsmentioning
confidence: 99%